Retail buying professionals' views on craft beers' sustainability - Aho, Kimmo (2022)
Craft beers have become a big global trend this millennium. A significant consumer segment is interested in craft beers and they have become more visible in retail as well. There is also a growing interest in sustainability issues of craft beer. Previous research on craft beer and its sustainability is focusing geographically outside of Finland and can therefore be specific to culture of origin. This study intends to supplement the existing knowledge and research in the Finnish context. The main research question this study tries to answer, is how retail buying professionals understand the craft beer’s sustainability. Additional questions were set to support the main research question. Those aims to answer which dimensions of sustainability retail buying professionals emphasize most and what are the most critical factors within the craft beer’s sustainability for them. The relevant theoretical framework was constructed mostly from the research papers among craft beer’s sustainability issues and tensions around them. These covered the ecological, economic, and social dimensions of craft beer in different markets and tensions in corporate social responsibility. Study’s approach was qualitative and 11 professional buyers working in retail were interviewed to explore their views on sustainability issues relating to craft beer produced in Finland. The interviews were recorded, transcribed, and analysed to produce the data which was compared with the theory. The most important results include gender equality among the people working in the craft brewing process, package recycling and logistics. The results reveal that even if gender equality is important, the understanding of this equality varies and is tensioned, as especially older male respondents did not notice it to the extent that female or younger male respondents did. Package recycling and logistics were discussed more concurrently, showing the significance of belonging to Palpa system and the importance of well-organized logistics. The results are at disposal for Finnish craft breweries who can apply them for improving their sustainability work to better meet the retail buying professionals’ needs.